Construction of Utility Tunnel power supply and distribution system - Shang, Jiankang; Zhang, Zheng; Zhou, Yunteng; Qin, Lulu; Wang, Yongcai; Niu, Zhao; Ding, Lingyan; Yin, Fuli (Transactions on Engineering and Technology Research, 2024)
As an underground structure that can accommodate multiple municipal pipelines, the utility tunnel can not only coordinate the planning, construction, and management of various municipal pipelines, but also achieve intensive development of urban underground space. In theory, any municipal pipeline can be included in the utility tunnel, thereby eradicating phenomena such as "road zippers" and "aerial spider webs" in the urban construction process. As a massive underground structure, the utility tunnel has its own electricity demand. Only by constructing a safe and stable power supply and distribution system inside the pipe gallery can it effectively ensure personal safety and the reliability of pipeline operation.